Dose response assessment of silica exposure and poisoning of construction workers - Xiao, Peng (2024)
Airborne exposure to silica, below statutory industrial standards, can cause silica exposure and poisoning in construction workers at higher rates than predicted. This research aimed to assess the respiratory health of construction workers exposed to silica from tiles, bricks, mortar, and concrete. The study found a positive correlation between construction material dust and fume exposures and workplace seniority. Silica poisoning was dose-dependent on cumulative silica dust or fumes exposure. The average industrial silica particles and emissions BMDLs were 0.68 and 0.30 mg year/m3, respectively. Silica dust and fume BMDLs for silica poisoning were 0.02 mg/m3 and 0.01 mg/m3, respectively. The study concluded that the current exposure levels for silica in China should be re-evaluated, and operational cumulative exposure limits should be established for better prevention of silica poisoning. The study also noted that disparities in sensitivity to silica poisoning may be related to genetic factors and gene-environment interactions.